Tspan8, CD44v6 and alpha6beta4 are biomarkers of migrating pancreatic cancer-initiating cells - Wang, Haobin; Rana, Sanyukta; Giese, Nathalia; Büchler, Markus W.; Zöller, Margot (International journal of cancer, 2013)
Pancreatic adenocarcinoma (PaCa) being the deadliest cancer is partly due to early metastatic spread. Thus, we searched for PaCa-initiating cell (PaCIC) markers with emphasis on markers contributing to metastatic progression. PaCIC were enriched from long-term and freshly established lines by repeated selection for spheroid or holoclone growth in advance of evaluating PaCIC markers. Sphere and holoclone formation steeply increased by recloning and remained stable thereafter. Cells not forming spheres or holoclones died on recloning. PaCIC enrichment in spheres and holoclones was accompanied by increased motility, anchorage independence and upregulated CXCR4 expression. After subcutaneous injection in NOD/SCID mice tumorigenicity and, impressively, recovery of metastasizing tumor cells in peripheral blood, spleen, bone marrow, lung and pancreas was strongly increased in spheres and holoclones. PaCIC enrichment in spheres and holoclones was accompanied, besides CXCR4, by upregulated CD44v6, alpha6beta4, weakly CD133 and tetraspanin Tspan8 expression. Notably, CD44v6, alpha6beta4, CXCR4 and Tspan8 expressing PaCa cells had a growth advantage in vivo and became dominating in migrating and in distant organs settled tumor cells. This is the first report showing that CD44v6, alpha6beta4, Tspan8 and CXCR4 are biomarkers in PaCIC allowing for long-term survival, expansion and migration in immunocompromised mice. The stability of the percentage of PaCIC in long-term and freshly established lines after a roughly 8-fold enrichment by cloning indicates PaCIC, though required for long-term survival, concomitantly depending on support by non-CIC.